"Feeling the waste" evidence from consumers' living in Gaza Strip camps. Issue 7 (15th September 2020) - Raab, Katharina; Wagner, Ralf; Salem, Mohammed
Abstract : Purpose: This paper aims to quantify the impact of antecedents (frustration, locus of control, spirituality, and religion and attention to social-comparison information) on the intensity of emotional outcomes of consumers' disposal behaviour. Design/methodology/approach: A structural equation model fitted with PLS was used to evaluate data obtained from 323 self-administered questionnaires filled out in a stratified random sample of respondents living in Gaza Strip camps. Findings: Spirituality and religion, and attention to social-comparison information have the highest impacts on emotional outcomes related to consumer disposal behaviour. Research limitations/implications: Spirituality and religion are seldom considered in previous consumer research, but they turn out to have high relevance for disposal-related emotions. Originality/value: To the best of the authors' knowledge, this is the first study investigating disposal-related emotions. Moreover, it is also the first study combining the impact of frustration, locus of control, perceived self-efficacy, spirituality and religion and attention to social-comparison information on emotional outcomes related to consumers' disposal behaviour.